Sliding Mode Based Nonlinear Control of a Three-Level NPC-Type DC-DC Bidirectional Converter for HV Applications - Ngoune, Jean-Paul; Etouke, Paul Owoundi; Ekemb, Gabriel; Cham, Julius D.; Boum, Alexandre T. (IAES Indonesian Section, 2025)
This paper proposes the design and a comparative study of three sliding modebased controllers—sliding mode control (SMC), fuzzy logic sliding mode control (Fuzzy-SMC), and ANFIS sliding mode control (Anfis-SMC)— applied to a newly designed DC-DC isolated bidirectional converter featuring a three-level neutral point clamped (3L-NPC) topology. Utilizing single phase shift (SPS) modulation enabled by a simplified analytical model, the controllers demonstrate strong robustness against load disturbances and input voltage variations, while ensuring accurate reference voltage tracking in both Boost and Buck modes. Comparative analysis shows that all three controllers outperform the traditional PI controller across most performance metrics. Voltage balancing is effectively maintained through an auxiliary inductive circuit. The investigated control schemes are validated via MATLABSimulink simulations, confirming their suitability for the efficient control of the studied converter.